Optimal pre-treatment for acute exposure to the organophosphate dicrotophos - Lorke, Dietrich; Petroianu, Georg (Current pharmaceutical design, 2017)
Background: Reversible cholinesterase inhibitors, when given prophylactically before exposure to organophosphates, are able to decrease organophosphate-induced mortality. However, the efficacy of pyridostigmine, the only pre-treatment substance approved by the US Federal Drug Administration, is unsatisfactory. Methods: In search of a better prophylactic compound, we determined in vivo the protection conferred by five cholinesterase inhibitors (ranitidine, physostigmine, tacrine, K-27 and pyridostigmine), which were administered in equitoxic dosage (1/4 of LD01) 30 minutes before exposure to the organophosphate dicrotophos. Efficacy was measured in rats by Cox analysis calculating the relative risk of death (RR), RR being 1 for the reference group which received dicrotophos and no prophylaxis. Results: K-27 (RR=0.06), physostigmine (RR=0.15), pyridostigmine (RR=0.22) and tacrine (RR=0.28) significantly (p ≤ 0.05) reduced dicrotophos-induced mortality in comparison to the reference group (dicrotophos without pre-treatment), whereas ranitidine (RR=0.86) had no significant influence. The experimental oxime K-27, when given before dicrotophos exposure, conferred the best in vivo protection. This was significantly (p ≤ 0.05) more efficacious than pre-treatment with any other tested compound. The differences in efficacy between the second best compound, physostigmine, and the less efficacious substances (tacrine and pyridostigmine) were also statistically significant. Conclusion: These data indicate that K-27 can be considered a very efficacious prophylactic agent for organophosphate exposure.
Gesehen am 11.09.2018